Disengagement in work-role transitions - Niessen, Cornelia; Binnewies, Carmen; Rank, J. (Journal of Occupational and Organizational Psychology, 2010)
The present study examines whether disengagement from previous work-roles positively predicts adaptation to a new work-role (here, becoming self-employed) by reducing negative consequences of psychological attachment to these previous roles. Disengagement involves an individual's effort to release attention from thoughts and behaviours related to the previous work-role. A three-wave longitudinal study investigated the relationship between psychological attachment (measured as affective commitment) to a prior work-role, disengagement from the prior work-role, and adaptation to a new work-role [pursuit of learning, fit perceptions with self-employment, task performance over time]. Participants included 131 persons who recently founded a small business. Results indicated that psychological attachment to the past work-role was negatively related to pursuit of learning and fit with the new work-role. Disengagement from the past work-role was positively related to pursuit of learning in the new work-role, and buffered the negative relationship between psychological attachment and fit as well as task performance. © 2010 The British Psychological Society.